ANALISIS KEBIJAKAN PENDIDIKAN MADRASAH TAKMILIYAH DAN BOARDING - Nur Aini Farida; Nia Karnia; Ferianto Ferianto (Universitas Islam Negeri Sumatera Utara Medan, 2022)
Islamic religious learning at school, which is only two hours a week, makes parents aware of the importance of religious education as one of the provisions of life for their children. The origins of Madrasah Diniyah are similar to those of Islamic boarding schools, beginning with recitation in mosques, langar, and surau. Madrasas, as Islamic educational institutions, have emerged and developed along with the entry and development of Islam in Indonesia. The importance of religious education is also felt by several madrasas, which require their students to live in dormitories, or what we know as boarding.